Post-CMV Guillain-Barré Syndrome with Anti-GM2 Antibodies: Two Cases and a Review of the Literature - Manaud, Alice; Geraudie, Amandine; Viguier, Agnès; Mengelle, Catherine; Fortenfant, Françoise; Baudou, Eloïse; Cheuret, Emmanuel (Neuropediatrics, 2022)
Introduction Guillain-Barré syndrome (GBS) is an acute post-infectious inflammatory polyneuropathy of ubiquitous distribution. Cytomegalovirus (CMV) is the virus that is most frequently involved. All ages are affected but rare pediatric cases seem to show some distinctive features in terms of specificity and severity. Specific antibodies that target the peripheral nervous system have been identified in several forms of GBS in adults, such as anti-GM2 ganglioside antibodies in post-CMV GBS, which in most instances present as demyelinating polyneuropathies, with a more favorable progression and fewer complications.Materials and Methods This is a retrospective report on two cases of post-CMV GBS with a demyelinating disorder and positive for anti-GM2 IgM. The review of the literature examines five other cases of children with post-CMV GBS with anti-GM2 IgM.Results In terms of progression, our two cases of post-CMV GBS with a demyelinating disorder and anti-GM2 IgM are similar to the five other cases described in the literature. The CMV infection was asymptomatic or paucisymptomatic and involved girls (6/7), often presenting severe motor forms with frequent loss of the ability to walk (4/6), facial involvement (⅗), little respiratory involvement (⅙), and favorable progression with adapted treatment.Conclusion Post-CMV GBS with anti-GM2 IgM is a specific clinical spectrum that seems to affect children as it affects adults with a predominance among females, demyelination, and severe motor involvement, but a good prognosis. On the other hand, unlike adults, the use of assisted ventilation does not seem to be more frequent.
Keywords: child; Guillain-Barré syndrome; anti-GM2 antibodies; cytomegalovirus